1978
DOI: 10.1017/s0022029900016204
|View full text |Cite
|
Sign up to set email alerts
|

The reaction of αs1- and β-casein with ferrous ions in the presence of oxygen

Abstract: The reaction of a^-and /ff-casein with ferrous ions and 0 2 has been studied. It has been found that phosphoseryl residues present in these proteins rapidly catalyse the oxidation of iron from the ferrous to the ferric state with the formation of stable ferric-phosphoprotein complexes and the consumption of the theoretical amount of O 2 . When, however, the phosphoseryl residues occurred in groups, the formation of ferric complexes was accompanied by uptakes of O 2 in quantities significantly in excess of that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…The observation that casein is antioxidative is in agreement with other reports on the antioxidant activity of casein (Tannenbaum et al 1969;Manson & Cannon, 1978;Laakso, 1984;Truby et al 1987). Taylor & Richardson (19806) reported that the PI decreased when casein (pH 6-7) was heated at 130 °C for 30 min.…”
Section: Antioxidant Activity Of Caseinsupporting
confidence: 92%
“…The observation that casein is antioxidative is in agreement with other reports on the antioxidant activity of casein (Tannenbaum et al 1969;Manson & Cannon, 1978;Laakso, 1984;Truby et al 1987). Taylor & Richardson (19806) reported that the PI decreased when casein (pH 6-7) was heated at 130 °C for 30 min.…”
Section: Antioxidant Activity Of Caseinsupporting
confidence: 92%
“…Caseins may also act as antioxidants because they have the ability to bind prooxidant metals to their phosphoserine residues [6,11], which inhibits the catalytic effect of the metals [1]. The present study showed that iron added as ferrous sulphate was bound completely to the casein molecules in sodium caseinate at added iron concentrations up to 4 mmol·L −1 (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…The formation of casein-iron complexes induces the oxidation of iron from the ferrous state to the ferric state [11]. The characteristics of different iron complexes as donors to caseins were investigated by Hegenauer et al [6].…”
Section: Introductionmentioning
confidence: 99%
“…Casein phosphopeptides have interesting physicochemical properties such as the formation of soluble complexes with bi-or trivalent metals (Oesterberg, 1966;Manson & Cannon, 1978), or the stabilization of Ca phosphate solutions against precipitation of tricalcium phosphate (Reeves & Latour, 1958). This latter property led to speculation that phosphopeptides might favourably influence intestinal Ca solubility (Naito el al.…”
mentioning
confidence: 99%